Learnings From Community-Based Small-Scale Irrigation in Tribal Areas of Jharkhand, India - Singh, Pratyush; Sharma, Stuti; Bihari, Bipin (World Bank, Washington, DC, 2020)
JOHAR is a pioneer in enabling tribal communities to be an integral stakeholder in development by ensuring availability, accessibility and utilization of water resources for agricultural development. JOHAR supports 200,000 small and marginal farmers in primarily rainfed, backward, drought prone, upland and tribal areas of Jharkhand. It facilitates a unique approach, that of "community-led irrigation" which brings water directly to the fields, and fosters community ownership from the onset of project conception, to survey and implementation, right through to operations and maintenance. This note highlights JOHAR's focus on promoting such an approach through engaging the community, particularly women in planning, implementation, monitoring and overall management of their irrigation infrastructure.